MEDICINES SUPPLY MANAGEMENT AND TOOLS HEALTH SYSTEM WITH LAN ON PT. RAJAWALI NUSINDO CAB. JAKARTA - Ring Apriyanti; Dra. Ida Ayu Wiastiti, MKom (Jurnal Sistem Informasi, 1997)
The development of the business world requires fast information flow, accurate yet practical. Moreover for companies engaged in the trafficking of drugs and medical devices, in which inventories are managed very much. With LAN system, these problems can be solved because the LAN systems can provide information automatically inter-related units.